2010
DOI: 10.1053/j.gastro.2010.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Epithelial–Mesenchymal Hedgehog Signaling Characterizes Barrett's Metaplasia

Abstract: Background & Aims-The molecular mechanism underlying epithelial metaplasia in Barrett's esophagus remains unknown. Recognizing that Hedgehog signaling is required for early esophageal development, we sought to determine if the Hedgehog pathway is reactivated in Barrett's esophagus, and if genes downstream of the pathway could promote columnar differentiation of esophageal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
208
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(218 citation statements)
references
References 51 publications
9
208
1
Order By: Relevance
“…12 Re-establishment of SHH/BMP4 signaling and SOX9 expression in Barrett's esophagus may reset the esophageal epithelium to a time when columnar cells line a primordial esophagus. 23 Bile acid upregulated the expression of SHH ligands, PATCH1, stromal BMP4, and subsequently SOX9, in the esophageal squamous epithelium. 16,23 A high SHH expression level was seen in nongoblet columnar-lined human esophagus compared with squamous line esophagus, but the level significantly decreased in Barrett's mucosa, indicating SHH might be an important initial factor in the induction and maintenance of a columnar phenotype.…”
Section: Cdx2 Sox9mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Re-establishment of SHH/BMP4 signaling and SOX9 expression in Barrett's esophagus may reset the esophageal epithelium to a time when columnar cells line a primordial esophagus. 23 Bile acid upregulated the expression of SHH ligands, PATCH1, stromal BMP4, and subsequently SOX9, in the esophageal squamous epithelium. 16,23 A high SHH expression level was seen in nongoblet columnar-lined human esophagus compared with squamous line esophagus, but the level significantly decreased in Barrett's mucosa, indicating SHH might be an important initial factor in the induction and maintenance of a columnar phenotype.…”
Section: Cdx2 Sox9mentioning
confidence: 99%
“…23 Bile acid upregulated the expression of SHH ligands, PATCH1, stromal BMP4, and subsequently SOX9, in the esophageal squamous epithelium. 16,23 A high SHH expression level was seen in nongoblet columnar-lined human esophagus compared with squamous line esophagus, but the level significantly decreased in Barrett's mucosa, indicating SHH might be an important initial factor in the induction and maintenance of a columnar phenotype. 16 This is consistent with our findings that SHH and BMP4 were expressed in the nongoblet columnar mucosa of most cases in both the Barrett's and control groups.…”
Section: Cdx2 Sox9mentioning
confidence: 99%
See 1 more Smart Citation
“…To date most effort has focussed on the homeobox genes Cdx1 and 2 which, in contrast to the dramatic effect observed when ectopically expressed in the murine stomach [8], fail to induce intestinalisation when over-expressed in the esophagus. Other transcription factors examined have included Hedgehog [9] and another critical signalling molecule in embryonic development called BMP4 [10], which have generally failed to induce phenotypic intestinalisation and in particular goblet cells.The aim of this paper was therefore to explore whether the helix-loop-helix transcription factor Math1/Atoh1, which is required for the differentiation of the three secretory cell lineages in the intestine (enteroendocrine, Paneth and goblet cells), could induce intestinalisation of an esophageal cell line. In order to explore this Kong et al [11] first confirmed earlier reports that this gene is over-expressed in Barrett's esophageal tissues [12].…”
mentioning
confidence: 99%
“…To date most effort has focussed on the homeobox genes Cdx1 and 2 which, in contrast to the dramatic effect observed when ectopically expressed in the murine stomach [8], fail to induce intestinalisation when over-expressed in the esophagus. Other transcription factors examined have included Hedgehog [9] and another critical signalling molecule in embryonic development called BMP4 [10], which have generally failed to induce phenotypic intestinalisation and in particular goblet cells.…”
mentioning
confidence: 99%